(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
The nursing profession plays a pivotal role in healthcare quality improvement, with nursing-sensitive indicators serving as critical metrics for evaluating patient care outcomes. This paper examines the evolution, implementation, and impact of nursing-sensitive quality indicators (NSIs) within contemporary healthcare systems. Through a comprehensive analysis of current literature and evidence-based practices, this study explores how NSIs contribute to continuous quality improvement (CQI) initiatives, patient safety enhancement, and overall healthcare delivery optimization. The research synthesizes findings from recent studies on quality improvement frameworks, explores the relationship between nursing practices and patient outcomes, and identifies emerging trends in quality measurement. Key findings indicate that effective implementation of NSIs requires systematic approaches, interprofessional collaboration, and sustained organizational commitment. The paper concludes with recommendations for advancing nursing quality initiatives and implications for future practice and research.